One Health serosurveillance of anti-SARS-CoV-2 antibodies in domestic animals from the metropolitan area of Panama - Sulamith Del C. Pacheco; Alanis J. Jimenez; Giselle A. Rangel; Claudia Del C. Rengifo-Herrera (Veterinary World)
Background and Aim: The COVID-19 pandemic, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has raised concern regarding anthropozoonotic transmission to domestic animals, posing potential public and veterinary health risks. Latin America remains underrepresented in seroepidemiological assessments of such zoonotic spillover. This study aimed to detect anti-SARS-CoV-2 antibodies in domestic dogs and cats in Panama using a One Health surveillance framework.